Commentary: The importance of exploring dose‐dependent, subtype‐specific, and age‐related effects of maltreatment on the HPA axis and the mediating link to psychopathology. A response to Fisher (2017). (September 2017) - White, Lars O.; Ising, Marcus; von Klitzing, Kai; Sierau, Susan; Michel, Andrea; Klein, Annette M.; Müller‐Myhsok, Bertram; Uhr, Manfred; Crowley, Michael J.; Kirschbaum, Clemens; Stalder, Tobias
Abstract : We greatly appreciate Dr. Fisher's commentary that provides an excellent backdrop and well‐considered perspective on our findings. We agree that our results mesh well with previous work documenting hypocortisolism among youth who experienced early adversity, especially neglect. Moreover, as also perceptively noted by Dr. Fisher, our cross‐sectional data provide support for the notion that hypocortisolism is not simply a transient phenomenon, but, rather, a persistent pattern characterizing maltreated youth. Specifically, the consistency of the between group effect (from age 9.69 onwards) on a multimonth index of cumulative cortisol and the dose‐dependent gradient of cortisol secretion within the maltreated group, which was related to the number of subtypes and the length of exposure to maltreatment, lend weight to this view. Abstract : Read the related Commentary at doi: 10.1111/jcpp.12719